Análisis jurídico de la evolución del derecho laboral en el Ecuador frente a la digitalización y el teletrabajo desde el año 2020 hasta el año 2024. - Santana Ruiz Carol Allison (2025)
The objective of this research project, entitled "Legal Analysis of the Evolution of Labor Law in Ecuador in the Face of Digitalization and Teleworking from 2020 to 2024," is to significantly study how digital transformation and teleworking have influenced the execution of work activities and Ecuadorian legal regulations since the pandemic and lockdown we experienced years ago, which forced governments across the country to implement a culture of teleworking or remote work out of necessity. This revealed the immature system of labor law in Ecuador, as the limited regulation of digital work meant that, in many cases, the labor rights of individual workers were not respected. The research begins with a historical review of labor law in Ecuador, from its beginnings in the 19th century to its most recent constitutional and legislative reforms. The profound changes brought about by the onset of the health crisis are evident, leading to the adoption of the Humanitarian Support Law and ministerial agreements on teleworking. These reduced the chances of obtaining job continuity, but left unanswered questions about digital disconnection, remote work hours, personal data protection, social security, collective labor rights, and decent working conditions from home. The rationale for this research lies in the urgent need to assess whether the Ecuadorian legal system has managed to adapt to the new digital labor context, and if so, whether it successfully guarantees, while avoiding any type of discrimination and the full observance of the fundamental rights of all those who carry out their work under the various digital forms or modalities associated with it. Therefore, this study aims to contribute to the formulation of proposals to strengthen current regulations, as well as to generate a space that more fairly and more contemporaryly addresses the regulation of teleworking and the digital forms attributable to it. This work applied qualitative methodology, with a dogmatic-legal, historical-logical, and comparative approach. Research methods were applied: document review, regulatory review, doctrinal analysis, and surveys conducted with a sample of workers who perform their jobs using digital tools, both in the public and private sectors. The expected outcome is an accurate diagnosis of the current situation of teleworking and the digitalization of the labor market in Ecuador, the identification of regulatory gaps regarding some forms of digital work, and the development of viable legal recommendations that guarantee compliance with fair, current, and inclusive working conditions. The aim is to contribute to the regulations that must accompany the digital transformation process, always benefiting labor rights and, of course, enabling a sustainable transition to the future of work in the country.